MASYUMI PARTY AND UTOPIA: THE IMPLEMENTATION OF POLITICAL TRIAS IN SULAWESI IN 1950-1953 - Amri, Khaerul; Makkelo, Ilham Daeng; Edi, Bambang Sulistyo (Kementerian Pendidikan dan Kebudayaan, 2020)
This paper focuses on the application of Political Trias in Sulawesi Province after re-declaring as a part of NKRI. Method used in this research is historical method, which explains research problem based on historical perspective. Its procedure includes four steps, finding and collecting data (heuristic), critique source (selecting data), interpretation, and historiography. The result of this study indicates that the application of Political Trias in Sulawesi had underground various governance adjustments as a form of power sharing. The formulation of power distribution changed in the early days of independence, then colored by the presence of political parties’ interests at the local level. One of the parties that succeeded in playing political arena in Sulawesi was the Masyumi Party